2011
DOI: 10.2337/db10-1281
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 Reduces Glucose Uptake in Human Skeletal Muscle In Vivo and In Vitro

Abstract: OBJECTIVEEndothelin (ET)-1 is a vasoconstrictor and proinflammatory peptide that may interfere with glucose uptake. Our objective was to investigate whether exogenous ET-1 affects glucose uptake in the forearm of individuals with insulin resistance and in cultured human skeletal muscle cells.RESEARCH DESIGN AND METHODSNine male subjects (aged 61 ± 3 years) with insulin resistance (M value <5.5 mg/kg/min or a homeostasis model assessment of insulin resistance index >2.5) participated in a protocol using saline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
43
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 30 publications
(43 reference statements)
7
43
0
Order By: Relevance
“…*p <0.05; **p <0.01; ***p <0.001 uptake at the 100 nmol/l concentration in insulin-resistant muscle cells (+9±4.6%; p <0.05; n =6) (Fig. 4b), as observed by others in type 2 diabetic patients [22]. We confirmed that nNOS expression remained reduced in cultured myocytes, as in entire muscles (Fig.…”
Section: +supporting
confidence: 77%
“…*p <0.05; **p <0.01; ***p <0.001 uptake at the 100 nmol/l concentration in insulin-resistant muscle cells (+9±4.6%; p <0.05; n =6) (Fig. 4b), as observed by others in type 2 diabetic patients [22]. We confirmed that nNOS expression remained reduced in cultured myocytes, as in entire muscles (Fig.…”
Section: +supporting
confidence: 77%
“…Among the regulated genes there was Edn1 (↑ 1,85) which impairs insulin-stimulated glucose uptake (Shemyakin et al 2010). This confirms our hypothesis that GDF8 action could occur through the Fig.…”
Section: Discussionsupporting
confidence: 76%
“…This overexpression of let-7 was associated with a let-7-mediated repression of components of the insulin/PI3K/mammalian target of rapamycin pathway, including abundance of the insulinlike growth factor receptor, the insulin receptor, and insulin receptor substrate-2 (47). Interestingly, insulin-stimulated Akt phosphorylation was not reduced in myotubes from T2DM patients, indicating that the function of the insulin-PI3K axis is preserved (40). This could be due to the more modest endogenous overexpression of let-7 in muscle from T2DM subjects (ϳ50%) compared with transgenic overexpression (6-to 10-fold) (47).…”
Section: Discussionmentioning
confidence: 89%
“…However, in myotubes derived from T2DM patients, IL-13-induced metabolic responses were impaired, with only a significant effects on glycogen synthesis and glucose oxidation noted. We have previously noted impaired metabolic responses to endothelin 1 (40) and IL-6 (21) in cells from derived T2DM patients, which may be indicative of a general metabolic impairment that persists in these cells.…”
Section: Discussionmentioning
confidence: 99%